(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence and severity of malnutrition among children with congenital heart disease treated in the Pediatric Cardiac Surgery Intensive Care Unit, Cho Ray Hospital. Subjects and methods: A descriptive cross-sectional study was conducted using data extracted from the electronic medical record system of pediatric patients with congenital heart disease admitted to the Pediatric Cardiac Surgery Intensive Care Unit, Cho Ray Hospital from August 2025 to December 2025. Results: Among children aged 0 to 60 months, the prevalence of underweight was 66.7%, stunting was 54.2%, and wasting was 39.6%. In the age group of over 5 to 10 years, 43.5% of children were underweight and 43.4% were stunted. Among children aged over 10 to 16 years, 11.8% were classified as thin, and 5.9% were identified as obese. Conclusion: The prevalence of malnutrition among children with congenital heart disease remains high across all forms of malnutrition and warrants targeted nutritional interventions. Children aged 0 to 60 months exhibited a higher prevalence of malnutrition compared with older age groups. In addition, obesity was observed in children aged over 10 to 16 years.